Eco-Enzyme Production from Household Organic Waste for Natural Cleaning Solutions - Suri, Wiranda Intan; Ratnawati, Beata; Tunggadewi, Andini Tribuana; Dellarosa, Luvy; Hidiya, Miesriany; Prasetya, Dimas Ardi; Paramitadevi, Yudith Vega; Wahdi, Emil Wahdi; Saputra, Septian Fauzi Dwi; Jannah, Nurul; Kartini, Sylvi Aprilia; Afigi, Nando (Riwayat: Educational Journal of History and Humanities, 2025)
Household activities generate large amounts of organic waste. Improper waste management can negatively impact the environment. Several areas, including Mulyaharja in Bogor, still face difficulties in managing organic waste. This is because the practice of sorting and processing organic waste has not yet been widely introduced and implemented. An alternative solution to reduce the negative impact of poor organic waste management on the environment is to process it into eco-enzymes. In addition to reducing the amount of waste disposed of in landfills, eco-enzymes can also function as a natural cleaning solution for daily household use. To introduce this processing method, a sustainable waste processing program was carried out in Mulyaharja through two activities. The first activity was the socialization of the definition and processing of organic waste, as well as the types of organic waste that can be used to produce eco-enzymes. The second activity was hands-on training in processing organic waste into eco-enzymes, so that the community could fully understand the tools, materials, and stages of its production. The main ingredients in making eco-enzymes are fruit and vegetable peel waste, molasses, and water. After the eco-enzyme solution was ready, this solution could be used to clean toilets, bathrooms, floors, and kitchen surfaces. The results of the program showed an increase in community knowledge and skills in processing organic waste, as well as increased adoption of environmentally friendly cleaning products as alternatives to chemical cleaners.